Ceramic reinforced iron-based composite coating, preparation method and application
The AlN precipitation-enhanced Fe-based composite coating is generated in situ by laser cladding, which solves the problem of poor performance of ceramic particle-enhanced iron-based composite coating materials in the prior art, and realizes a coating with high hardness and high thermal conductivity, which significantly improves thermal shock resistance and service life.
Patent Information
- Application Number
- CN202411683532.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, when preparing iron-based composite coatings with ceramic particles enhanced, the material performance is poor, the thermal conductivity is low, and the thermal expansion coefficient is largely different from that of stainless steel, resulting in thermal stress generation and cracks, reducing service life.
The laser cladding method is used to generate a Fe-based composite coating with enhanced precipitation of fine diffuse AlN in situ, and a pre-alloy powder containing nitrogen is prepared by water atomization method to ensure that the AlN particles form an efficient thermal conduction path in the matrix.
It significantly improves the hardness and thermal conductivity of the stainless steel surface coating, enhances the thermal shock resistance and service life, and the coating does not crack or peel after 100 cycles of thermal shock.
Smart Images

Figure CN119506866A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of powder metallurgy and surface engineering, and particularly relates to a ceramic-reinforced iron-based composite coating, a preparation method and an application thereof. Background Art
[0002] Austenitic stainless steel with high Cr and Ni content has excellent oxidation resistance and corrosion resistance. It is mostly used for high-temperature heat-resistant parts, such as the grate plate material in the chain grate machine, the main equipment for pellet production. It not only serves for a long time in a high-temperature environment (about 800°C), but also has to withstand the test of thermal shock due to the reciprocating motion of the grate plate between high and low temperature ranges. Although stainless steel has excellent resistance to high-temperature oxidation, it also has disadvantages such as low hardness and poor wear resistance. In order to improve the surface hardness of stainless steel and reduce wear, the method of adding a coating to the surface of stainless steel is often used, such as preparing a layer of steel-based composite material coating reinforced with hard ceramic particles on its surface. Although this method can greatly improve the surface hardness of stainless steel and improve wear resistance, it often ignores the service life of the coating under thermal shock conditions. Commonly used hard ceramic particles are mostly carbide particles, such as niobium carbide, tungsten carbide, etc. The thermal conductivity of this type of carbide is low, only 14-29W / (m·K), which is not conducive to the rapid conduction of heat. In addition, the thermal expansion coefficient is very different from that of stainless steel, which often leads to thermal stress and induced cracks, thus causing the matrix to peel off and sharply reducing the service life.
[0003] The thermal conductivity of AlN ceramics is as high as 320W / (m·K), which is much higher than other ceramics, and has good thermal shock resistance and excellent thermal shock resistance. In addition, due to its small size effect, fine particles can form efficient heat conduction paths in the matrix, which help the rapid spread of heat in the matrix, thereby improving the thermal conductivity of the overall material.
[0004] The existing technology usually adopts the direct addition of ceramic particles and the element powder mixing method to prepare the ceramic particle reinforced iron-based composite coating. The ceramic particle addition method is prone to poor interface bonding between particles and the matrix, forming thermal resistance and hindering the effective transfer of heat. The inability to effectively transfer heat will cause thermal stress inside the material, which will cause thermal deformation.
[0005] The element powder mixing method often causes uneven distribution of elements due to the difference in density of two or more powders. This unevenness will be transferred to the final coating material, causing uneven distribution of ceramic particles and forming a "heat island effect". As a result, heat accumulates in the agglomerated area and cannot be effectively dissipated, which is also not conducive to improving the thermal shock resistance.
[0006] For AlN ceramic particles, if the finished particles are added, there is also the problem of high cost, because the large-scale preparation of pure AlN particles is extremely difficult. Summary of the invention
[0007] The purpose of the present invention is to provide a composite coating material, a preparation method and an application thereof, in view of the technical problem that the method for preparing a ceramic particle reinforced iron-based composite coating in the prior art results in poor material performance.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A ceramic-reinforced iron-based composite coating comprises a ceramic component and an alloy component. The ceramic component comprises AlN, the alloy component is an iron-based alloy, and the iron-based alloy comprises metallic aluminum. The composite coating material is obtained by laser cladding nitrogen-containing pre-alloyed powder.
[0010] In the technical solution of the present invention, laser cladding is used to generate a composite coating reinforced with ceramic particles in situ, which effectively improves the hardness of the stainless steel surface coating. AlN is used as a hard ceramic particle, and a Fe-based composite coating reinforced with fine dispersed AlN precipitation is obtained by in-situ generation. Because the theoretical thermal conductivity of AlN is as high as 320W / (m·K), which is much higher than other ceramics, it has good thermal shock resistance and excellent thermal shock resistance. In addition, due to its small size effect, the fine particles can form efficient heat conduction paths in the matrix, which help to quickly spread heat in the matrix, thereby improving the thermal conductivity of the overall material and alleviating interface cracking or coating cracking caused by thermal shock. In the coating material of the present invention, an iron-based pre-alloyed powder containing solid-solution N elements is used, and a Fe-based composite coating reinforced with AlN precipitation is generated by in-situ reaction by high-temperature rapid heating and rapid cooling by laser cladding. AlN mainly plays the role of increasing thermal conductivity, improving thermal shock resistance and improving service life.
[0011] As a preferred technical solution of the present invention, the mass proportion of the AlN in the iron-based composite coating is 0.15-0.5%.
[0012] If the proportion of AlN is too small, the hardness and thermal conductivity of the coating will not be greatly improved. If the proportion is too large, large-sized AlN particles will easily appear, resulting in a reduction in surface area. This is not conducive to forming an efficient heat conduction path, and the AlN ceramic itself is also prone to cracking under thermal shock.
[0013] Preferably, the iron-based alloy components include chromium, aluminum, nickel and iron, wherein the mass percentage of the chromium element is 14%-19%, the mass percentage of the aluminum element is 4%-7%, the mass percentage of the nickel element is 9%-14%, and the balance is iron. The nickel element is melted into the coating from the stainless steel during the laser cladding process.
[0014] Preferably, in the nitrogen-containing pre-alloyed powder, the mass content of the solid-solution nitrogen element is in the range of 0.05%-0.1%, the mass percentage of the chromium element is in the range of 5%-10%, the mass percentage of the aluminum element is in the range of 8-15%, and the balance is iron.
[0015] Cr mainly plays a role in solid solution strengthening. Chromium has a very high hardness and can improve the hardness and wear resistance of iron products, making them more resistant to physical damage such as friction, scratches and impacts. Al mainly plays a role in forming an aluminum oxide film at high temperature, increasing oxidation resistance and serving as a synthetic raw material for AlN.
[0016] If the chromium content is too high, the hardness of the final coating will be too high and it will be easy to crack, because Cr and Fe elements are very likely to generate brittle phases such as sigma phase under high temperature conditions, which seriously reduces the plasticity and toughness of the material. If the content is too low, the nitrogen content will be reduced. Because Cr and N have a good affinity, the increase of Cr helps to increase the N content in the water atomized powder.
[0017] Preferably, the particle size of the AlN is in the range of 0.2 μm-2 μm.
[0018] A method for preparing a composite coating material comprises the following steps:
[0019] Step S1, mixing the raw materials according to a weight ratio, and preparing nitrogen-containing pre-alloyed powder by water atomization under nitrogen protection for standby use;
[0020] Step S2: cladding the nitrogen-containing pre-alloyed powder onto an austenitic stainless steel substrate by laser cladding to form a ceramic particle composite coating.
[0021] In the preparation method of the present invention, nitrogen is added to the raw material for coating preparation by water atomization to form a nitrogen-containing pre-alloyed powder, and then the nitrogen-containing pre-alloyed powder is directly clad on a stainless steel substrate by laser to form a composite coating. The method can ensure that the coating contains a large number of submicron-sized AlN particles generated by in-situ reaction, which are well bonded to the substrate interface and have a clean phase interface. Because the theoretical thermal conductivity of AlN is as high as 320W / (m·K), which is much higher than other ceramics, it has good thermal shock resistance and excellent thermal shock resistance. The Fe-based composite material coating enhanced by fine dispersed AlN precipitation is generated in situ by laser cladding. Due to its small size effect, the fine particles can form efficient heat conduction paths in the matrix, which help the rapid propagation of heat in the matrix, thereby improving the thermal conductivity of the overall material.
[0022] As a more preferred embodiment, the particle size of the pre-alloyed powder is 100 μm-200 μm.
[0023] If the powder particle size is too small, it is easy to be blown away by the cladding airflow, causing losses; if the particle size is too large, it is not conducive to the solid solution of N into the powder during the powder making process.
[0024] As a more preferred embodiment, the power range of the laser is 500-1000W.
[0025] As a more preferred embodiment, the scanning speed of the laser is 5mm / s-15mm / s.
[0026] As a more preferred embodiment, laser cladding is performed under an inert gas, wherein the inert gas is argon gas, the flow rate of the argon gas is 5-20 L / min, and the flow rate of the powder feeding argon gas is 3-8 L / min.
[0027] Preferably, the raw materials include aluminum blocks, chromium blocks and iron blocks;
[0028] Alternatively, the raw materials include aluminum blocks and iron-chromium alloy blocks. The aluminum blocks have a purity of more than 97% and a size of 50-100 mm, and the iron-chromium alloy blocks have a particle size of about 5 mm-10 mm, contain 60-70% Cr elements, and have a purity of more than 96%.
[0029] The coating of the present invention is mainly applied to a stainless steel substrate, which is austenitic stainless steel, and its chemical composition is: 24.05% Cr, 19.05% Ni, 1.26% Mn, 0.46% Si, 0.08% C, P<0.03%, S<0.03%, and the balance is Fe. The thickness of the stainless steel substrate is not less than 0.5 mm.
[0030] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0031] The present invention adopts in-situ laser cladding to generate ceramic particles as the strengthening component in the coating, greatly improving the hardness of the stainless steel surface coating, adopts AlN as the hard ceramic particles, and in-situ generates fine dispersed AlN precipitation to strengthen the Fe-based composite material coating. Because the theoretical thermal conductivity of AlN is as high as 320W / (m·K), which is much higher than other ceramics, it has good thermal shock resistance and excellent thermal shock resistance.
[0032] Due to their small size effect, the fine particles can form efficient heat conduction paths in the matrix, which help the rapid propagation of heat in the matrix, thereby improving the thermal conductivity of the overall material. In the coating material of the present invention, N-containing iron-based pre-alloyed powder is used, and the AlN precipitation-enhanced Fe-based composite material coating is generated by in-situ reaction through high-temperature rapid heating and rapid cooling by laser cladding method. AlN mainly plays the role of increasing thermal conductivity, improving thermal shock resistance and improving service life. Through experimental verification, after 100 cycles of thermal shock, the coating did not have any form of cracks or peeling, and the bonding interface between the coating and the substrate was good. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope (SEM) image of the coating sample interface of Example 1 after 0 thermal shock;
[0034] Figure 2 The SEM image of the coating sample interface of Example 1 after 10 thermal shocks;
[0035] Figure 3 This is a scanning electron microscope (SEM) image of the coating sample interface of Example 1 after 50 thermal shocks;
[0036] Figure 4 This is a scanning electron microscope (SEM) image of the coating sample interface of Example 1 after 100 thermal shocks;
[0037] Figure 5 This is a schematic diagram of point selection for interface energy spectrum analysis of coating samples in Example 1;
[0038] Figure 6 for Figure 5 Energy spectrum of point 1 in ;
[0039] Figure 7 for Figure 5 Energy spectrum of point 2 in ;
[0040] Figure 8 for Figure 5 Energy spectrum of point 3 in ;
[0041] Fig. 9 This is a scanning electron microscope (SEM) image of the coating sample interface of Comparative Example 1 after five thermal shocks. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with test examples and specific implementation methods. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the content of the present invention belong to the scope of the present invention.
[0043] Unless otherwise specified, in the description of the specific embodiments of the present invention, the terms indicating the orientation or position relationship such as "up", "down", "left", "right", "center", "inside", "outside", etc. are all expressions based on the orientation or position relationship shown in the drawings, or the orientation or position relationship when the invented product / equipment / device is usually used. These terms of orientation or position relationship are only for the convenience of describing the scheme of the present invention or simplifying the description in the specific embodiments, so as to facilitate the technicians to quickly understand the scheme, rather than indicating or implying that a specific device / component / element must have a specific orientation, or be constructed and operated in a specific position relationship, and therefore cannot be understood as a limitation on the present invention.
[0044] In addition, if the terms "horizontal", "vertical", "overhanging", "parallel" and the like appear, it does not mean that the corresponding devices / components / elements are required to be absolutely horizontal or vertical or overhanging or parallel, but may be slightly tilted or have deviations. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but may be slightly tilted. Alternatively, it can be simplified to mean that the corresponding devices / components / elements are set in directions such as "horizontal", "vertical", "overhanging", "parallel", etc., and can have an error / deviation of ±10% relative to the corresponding direction setting, more preferably an error / deviation within ±8%, more preferably an error / deviation within ±6%, more preferably an error / deviation within ±5%, and more preferably an error / deviation within ±4%. As long as the corresponding device / component / element is within the error / deviation range, it can still achieve its role in the scheme of the present invention.
[0045] In addition, the expressions “first”, “second”, “third”, etc. that appear in the terms are merely descriptions used to distinguish the same or similar components and should not be understood as emphasizing or implying the relative importance of specific components.
[0046] In addition, in the description of the embodiments of the present invention, "several", "plurality" and "a number" represent at least 2. It can be any number such as 2, 3, 4, 5, 6, 7, 8, 9, and even more than 9.
[0047] In addition, in the description of the technical solution of the present invention, unless otherwise clearly specified / defined / restricted, the terms "set", "install", "connect", "connected", "provided with", "laid", and "arranged" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection, and can be welding, riveting, bolting, threading, and other commonly used connection means in the field. This connection can be a mechanical connection, an electrical connection, or a communication connection; it can be a direct connection, or an indirect connection through an intermediate medium, and it can be the internal connection of two elements.
[0048] In the present invention, percentages not particularly described are percentages by weight.
[0049] Example 1
[0050] The present embodiment provides a ceramic-reinforced iron-based composite coating, wherein the raw materials for preparation are as follows in percentage by mass: an aluminum block and an iron-chromium alloy block, wherein the aluminum block has a purity of 97.5% and a size of 50 mm; the iron-chromium alloy block contains 60% Cr element, has a purity of 96.5%, and a particle size of 10 mm;
[0051] Step S1, mixing the above raw materials according to weight ratio, and preparing nitrogen-containing pre-alloyed powder by water atomization under nitrogen protection, wherein the purity of the protective nitrogen gas is 99.9%. The nitrogen-containing pre-alloyed powder has a nitrogen content of 0.05%, a chromium content of 5%, an aluminum content of 11%, and the balance of iron;
[0052] Step S2: cladding the nitrogen-containing pre-alloyed powder onto an austenitic stainless steel substrate by laser cladding to form a ceramic particle-reinforced iron-based composite coating.
[0053] The austenitic stainless steel matrix is 310S stainless steel (chemical composition: 24.05% Cr, 19.05% Ni, 1.26% Mn, 0.46% Si, 0.08% C, P<0.03%, S<0.03%, balance Fe);
[0054] Specifically, the parameter information of laser cladding is: protective argon gas flow rate 10L / min, powder feeding argon gas flow rate 5L / min, laser power 1000W, and scanning speed 5mm / s.
[0055] The prepared coating material has a thickness of about 1.5 mm, and contains a large number of submicron-sized ceramic AlN particles generated by in-situ reaction, and the iron-based alloy includes iron, chromium, and aluminum elements. The proportion of AlN particles is 0.15%.
[0056] Example 2
[0057] This embodiment provides a composite coating material, which includes the following raw materials in percentage by mass: an aluminum block and an iron-chromium alloy block, wherein the aluminum block has a purity of 98.5% and a size of 60 mm; the iron-chromium alloy block contains 70% Cr element, has a purity of 97.0%, and a particle size of 5 mm;
[0058] Step S1, mixing the above-mentioned raw materials according to a weight ratio, and preparing nitrogen-containing pre-alloyed powder by water atomization under the protection of nitrogen for standby use; the purity of the protective gas nitrogen is 99.9%; wherein, the nitrogen content of the nitrogen-containing pre-alloyed powder is 0.1%, the chromium content is 10%, the aluminum content is 8%, and the balance is iron.
[0059] Step S2: cladding the nitrogen-containing pre-alloyed powder onto an austenitic stainless steel substrate by laser cladding to form a ceramic particle-reinforced iron-based composite coating.
[0060] The austenitic stainless steel matrix is 310S stainless steel (chemical composition: 24.05% Cr, 19.05% Ni, 1.26% Mn, 0.46% Si, 0.08% C, P<0.03%, S<0.03%, balance Fe);
[0061] Specifically, the parameter information of laser cladding is: protective argon gas flow rate 5 L / min, powder feeding argon gas flow rate 8 L / min, laser power 800 W, and scanning speed 10 mm / s.
[0062] The prepared coating material has a thickness of about 1 mm, and contains a large number of submicron-sized ceramic AlN particles generated by in-situ reaction, and the iron-based alloy includes iron, chromium, and aluminum elements. The proportion of AlN particles is 0.5%.
[0063] Example 3
[0064] This embodiment provides a composite coating material, including the following preparation method:
[0065] Step S1, mixing the raw materials according to the weight ratio, and preparing the nitrogen-containing pre-alloyed powder by water atomization under the protection of nitrogen gas for use; the purity of the protective nitrogen gas is 99.9%. The nitrogen-containing pre-alloyed powder has a nitrogen content of 0.08%, a chromium content of 8%, an aluminum content of 15%, and the balance of iron;
[0066] Step S2: cladding the nitrogen-containing pre-alloyed powder onto an austenitic stainless steel substrate by laser cladding to form a ceramic particle-reinforced iron-based composite coating.
[0067] The austenitic stainless steel matrix is 310S stainless steel (chemical composition: 24.05% Cr, 19.05% Ni, 1.26% Mn, 0.46% Si, 0.08% C, P<0.03%, S<0.03%, balance Fe);
[0068] Specifically, the parameter information of laser cladding is: protective argon gas flow rate 20L / min, powder feeding argon gas flow rate 3L / min, laser power 500W, and scanning speed 15mm / s.
[0069] The prepared coating material has a thickness of about 0.5 mm. The coating contains a large number of submicron-sized ceramic AlN particles generated by in-situ reaction. The iron-based alloy includes iron, chromium, and aluminum elements. The proportion of AlN particles is 0.35%.
[0070] Example 4
[0071] This embodiment provides a composite coating material, including the following preparation method:
[0072] Step S1, mixing the above raw materials according to weight ratio, and preparing nitrogen-containing pre-alloyed powder by water atomization under nitrogen protection; the purity of the protective nitrogen gas is 99.9%. The nitrogen-containing pre-alloyed powder has a nitrogen content of 0.06%, a chromium content of 6%, an aluminum content of 13%, and the balance is iron;
[0073] Step S2: cladding the nitrogen-containing pre-alloyed powder onto an austenitic stainless steel substrate by laser cladding to form a ceramic particle-reinforced iron-based composite coating.
[0074] The austenitic stainless steel matrix is 310S stainless steel (chemical composition: 24.05% Cr, 19.05% Ni, 1.26% Mn, 0.46% Si, 0.08% C, P<0.03%, S<0.03%, balance Fe);
[0075] Specifically, the parameter information of laser cladding is: protective argon gas flow rate 10L / min, powder feeding argon gas flow rate 2L / min, laser power 700W, and scanning speed 12mm / s.
[0076] The prepared coating material has a thickness of about 0.8 mm, and contains a large number of submicron-sized ceramic AlN particles generated by in-situ reaction, and the iron-based alloy includes iron, chromium, and aluminum elements. The proportion of AlN particles is 0.25%.
[0077] According to the preparation method of Example 1, the composite coatings of Examples 1-4 were prepared respectively to obtain coating samples #1-#4;
[0078] The hardness test was performed on the above samples, and the test results are shown in Table 1 below:
[0079] Table 1 is the coating hardness test data
[0080] sample Example 1 Example 2 Example 3 Example 4 Matrix microhardness <![CDATA[142HV 0.5 ]]> <![CDATA[141HV 0.5 ]]> <![CDATA[147HV 0.5 ]]> <![CDATA[143HV 0.5 ]]> Coating hardness <![CDATA[468HV 0.5 ]]> <![CDATA[458HV 0.5 ]]> <![CDATA[454HV 0.5 ]]> <![CDATA[447HV 0.5 ]]>
[0081] It can be seen from the above hardness test results that the coating samples of Examples 1-4 have higher hardness, which is more than twice the hardness of the substrate without coating.
[0082] Furthermore, the coating samples of the above-mentioned Example 1 were subjected to a thermal shock resistance test. The specific test method was as follows: the coating samples of Examples 1-4 were placed in a ceramic crucible and then placed in a muffle furnace for heating at 800°C / 20min, then the samples were taken out for air cooling for 5min, and then the samples were placed in the muffle furnace for heating for 20min again. This cycle was repeated for 10, 50, and 100 different times of thermal shock simulation. The experimental results are shown in Figure 2. Figure 1-4 As shown, Figure 1 This is a scanning electron microscope (SEM) image of the coating sample interface of Example 1. Figure 2 This is the interface after 10 cycles of thermal shock. Figure 3 The interface after 50 cycles of thermal shock. Figure 4 The interface after 100 cycles of thermal shock; Figure 1-4The test shows that the coating prepared by the preparation method of the present invention has good impact resistance. After 100 cycles of thermal shock, the coating does not have any cracks or peeling, and the bonding interface between the coating and the substrate is good.
[0083] The coating of Example 1 was subjected to EDS energy spectrum analysis, specifically, Figure 5 As shown, the three points 1, 2, and 3 in the figure are performed. Figure 6-Figure 8 As shown, the element data of the three points are shown in Table 1 below:
[0084] Table 2 is a summary of the element contents of EDS energy spectrum analysis
[0085]
[0086]
[0087] From the results in Table 2, it can be seen that at positions 1 and 2, the atomic percentages of nitrogen and aluminum are approximately 1:1, which indicates that the materials at positions 1 and 2 are AlN ceramic particles.
[0088] Comparative Example 1
[0089] The product of the FeCrAl element powder mixing method without AlN ceramic particle reinforcement is prepared by uniformly mixing Fe, Cr and Al powders (particle size 100-200 microns) in a mixer in a mass ratio of 5:15:80, and cladding the nitrogen-containing pre-alloyed powder on an austenitic stainless steel substrate by laser cladding to form a ceramic particle reinforced iron-based composite coating.
[0090] The austenitic stainless steel matrix is 310S stainless steel (chemical composition: 24.05% Cr, 19.05% Ni, 1.26% Mn, 0.46% Si, 0.08% C, P<0.03%, S<0.03%, balance Fe);
[0091] Specifically, the parameters of laser cladding are: protective argon gas flow rate of 10 L / min, powder feeding argon gas flow rate of 5 L / min, laser power of 500 W, and scanning speed of 15 mm / s. A coating with a thickness of about 0.3 mm is obtained, and the coating does not contain ceramic AlN particles.
[0092] Furthermore, the coating samples of the comparative example were subjected to a thermal shock test. The specific test method was as follows: the coating samples were placed in a ceramic crucible and then placed in a muffle furnace for heating at 800°C / 20 min, then the samples were taken out for air cooling for 5 min, and then the samples were placed in the muffle furnace for heating for 20 min again. This cycle was repeated for 5 thermal shock simulations. The experimental results are shown in Figure 2. Fig. 9As shown in the figure, due to the lack of AlN to enhance heat conduction, large cracks have already occurred in the coating, even penetrating the interface between the substrate and the coating, and the coating has already failed.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A ceramic-reinforced iron-based composite coating, characterized in that: The composite coating material comprises a ceramic component and an alloy component, wherein the ceramic component comprises AlN, the alloy component is an iron-based alloy, and the iron-based alloy comprises aluminum. The composite coating material is obtained by laser cladding nitrogen-containing pre-alloyed powder.
2. The ceramic-reinforced iron-based composite coating according to claim 1, characterized in that: The mass proportion of the AlN in the iron-based composite coating is 0.15-0.5%.
3. The ceramic-reinforced iron-based composite coating according to claim 1, characterized in that: The iron-based alloy components include chromium, aluminum, nickel and iron. The mass percentage of the chromium element is 14%-19%, the mass percentage of the aluminum element is 4%-7%, the mass percentage of the nickel element is 9%-14%, and the balance is iron.
4. The ceramic-reinforced iron-based composite coating according to claim 1, characterized in that: In the nitrogen-containing pre-alloyed powder, the nitrogen content is 0.05%-0.1%, the mass percentage of the chromium element is 5%-10%, the mass percentage of the aluminum element is 8-15%, and the balance is iron.
5. A method for preparing a ceramic-reinforced iron-based composite coating according to any one of claims 1 to 4, characterized in that: The steps include: Step S1, mixing the raw materials according to a weight ratio, and preparing nitrogen-containing pre-alloyed powder by water atomization under nitrogen protection for standby use; Step S2: cladding the nitrogen-containing pre-alloyed powder onto an austenitic stainless steel substrate by laser cladding to form a ceramic particle-reinforced iron-based composite coating.
6. The preparation method according to claim 5, characterized in that: The particle size of the pre-alloyed powder is 100 μm-200 μm.
7. The preparation method according to claim 5, characterized in that: The thickness of the composite coating is 0.5 mm-1.5 mm.
8. The preparation method according to claim 5, characterized in that: The power range of the laser is 500W-1000W, and the scanning speed of the laser is 5mm / s-15mm / s.
9. The preparation method according to claim 5, characterized in that: Laser cladding is performed under an inert gas, wherein the inert gas is argon gas, the flow rate of the argon gas is 5-20 L / min, and the flow rate of the powder feeding argon gas is 3-8 L / min.
10. A stainless steel product comprising an austenitic stainless steel matrix, characterized in that: It also includes a ceramic-reinforced iron-based composite coating as described in any one of claims 1-4, or a ceramic-reinforced iron-based composite coating prepared by the preparation method as described in any one of claims 6-9.